GEORGIA'S ECONOMY IN THE SPACE OF CONTRADICTIONS BETWEEN REGIONAL POWERS - A. S. Degtev; A. Margoev; A. A. Tokarev (Vestnik MGIMO-Universiteta)
The article deals with the economic ties between Georgia and four countries neighbouring the Caucasus region: Russia, Turkey, Iran, and Kazakhstan. The authors focus their attention on regional analysis and, for comparison, give figures on Georgia's relations with three global players: the USA, the EU, and the PRC. The authors postulate at least three challenges to Russia’s interests in Georgia. First, both Georgian establishment and society regard integration with the EU and NATO as main goal of the state, which in case of NATO evidently contradicts Russian national interests. Second, from the economic point of view, the USA is no longer a financial driver of Georgian reforms. The EU, main trade partner of Georgia for the past 15 years, has replaced it. The CIS surpasses the EU in commodity turnover with Georgia, however it is in fact an amorphous organization that formally combines its member-states and lacks for common economic policy, unlike the European Union that acts as an integration association. Third, Chinese investment in Georgian infrastructure within the "New Silk Way" project serves as a ponderable alternative to Russian financial flow. For a comprehensive analysis of the situation the authors used some figures concerning commodity trade, FDI, cross-border financial flows, tourism, and transport development. Major pipeline branches, including the planned projects, are taken into account as well. The findings are based on the results of desk research, and on empirical data obtained through meetings with Georgian government officials.